Increasing Sawntimber Recovery by Target Size Reduction - Liew, Sung Fatt (1990)
Sawing timber with excessive oversize, undersize or poor sawing accuracy can result in a decreased sawntimber recovery. As timber gets scarcer and more expensive, there is a need for sawmillers to improve sawntimber recovery to enable them to remain in business. Statistical Lumber Size Control (SLSC) has wide recognition as a useful technique in increasing sawntimber recovery. The objectives of this study are; to apply the technique to monitor sawing accuracy and to appraise the economic benefit of Target Size Reduction (TSR). The study was done in three stages. Stage One involved the measurement of 100 boards (25 subgroups of 4 boards per subgroup) to establish the green target size and the existing recovery rate. In Stage Two, X-R Control Charts were drawn and used to monitor the sawing accuracy. The last stage assessed the net revenue improvement based on the TSR. The result showed that a 2% increase in recovery rate based on the nominal thickness of 7/8" (22.22mm) can increase the estimated net revenue by $293,912.00 for the first year of implementing a SLSC programme in a sawmill. The technique and X-R Control Charts are effective tools in improving the sawntimber recovery. However, in order to obtain a higher recovery improvement, it is necessary to improve the dimensioning device and the fence setting mechanism at the resaw machine.